Antibacterial urea resin and preparation method thereof

By introducing oxidized quaternized chitosan into the urea resin, the problems of high formaldehyde emission and lack of antibacterial properties of traditional urea resins are solved, and the comprehensive improvement of high gluing strength, low formaldehyde emission and excellent antibacterial properties are achieved, which is suitable for applications with high environmental protection requirements.

CN119735773AActive Publication Date: 2025-04-01JINING GAOXING TIMBER PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411992274.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-01
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Traditional urea resins have problems with high formaldehyde emission and lack of antibacterial properties, which are difficult to meet increasingly stringent environmental protection and hygiene requirements.

Method used

By introducing oxidized quaternized chitosan, the preparation process of urea resin is optimized, its solid content, viscosity and antibacterial properties are improved, while reducing the free formaldehyde content.

Benefits of technology

It significantly improves the comprehensive performance of urea resin, including high gluing strength, low formaldehyde emission and excellent antibacterial properties, meets stricter environmental protection requirements and is suitable for application scenarios with high environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223900550000101
    Figure BDA0005223900550000101
Patent Text Reader

Abstract

The invention relates to the technical field of resin, in particular to antibacterial urea resin and a preparation method thereof. The preparation method comprises the following steps: modifying chitosan by using dimethylaminochloroethane hydrochloride as a quaternization reagent, oxidizing by using potassium periodate to obtain quaternized oxidized chitosan, and reacting with urea and formaldehyde by using the quaternized oxidized chitosan as a cross-linking agent to obtain the antibacterial urea resin. The antibacterial urea resin prepared by the invention has high solid content and viscosity, moderate curing time, excellent antibacterial property and extremely low free formaldehyde content, so that the antibacterial urea resin has excellent environmental protection property and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resins, and in particular to an antibacterial urea resin and a preparation method thereof. Background Art

[0002] Urea resin is an important thermosetting resin. It is widely used in plywood, furniture manufacturing, decorative materials and other fields due to its low cost, excellent performance and mature process. However, traditional urea resin has the problem of high free formaldehyde content. It will release formaldehyde during use, causing serious harm to the environment and human health, and it is difficult to meet the increasingly stringent environmental protection standards. In addition, urea resin itself does not have antibacterial properties. It is easy to breed bacteria and mold in a humid environment, affecting the service life and hygienic performance of the product, further limiting its application in fields with high environmental protection and high hygienic requirements. With the increasingly stringent environmental protection regulations and people's concern about health and safety, the development of urea resin with low formaldehyde release and antibacterial properties has become a hot spot and difficulty in current research.

[0003] Chitosan, a natural polysaccharide with a wide range of sources, has attracted widespread attention due to its good biocompatibility, antibacterial properties and environmental protection characteristics. The introduction of chitosan can give urea resin certain antibacterial properties and improve its environmental performance. However, the dispersibility of chitosan in urea resin is poor, and the binding force with the network structure of urea resin is insufficient, resulting in limited modification effect. Summary of the invention

[0004] In view of this, the object of the present invention is to provide an antibacterial urea resin and a preparation method thereof, so as to solve the problems of high formaldehyde emission and lack of antibacterial performance of urea resin.

[0005] Based on the above purpose, the present invention provides a method for preparing an antibacterial urea resin, comprising the following steps:

[0006] (1) adding chitosan to an N-methyl-2-pyrrolidone solution containing 0.8 wt%-1.2 wt% acetic acid, stirring for 20-40 min, then adding sodium iodide, heating to 55-65° C., stirring for 20-40 min, then adding dimethylaminoethyl chloride hydrochloride, continuing to stir for 2.5-3.5 h, finally washing, and drying under reduced pressure to obtain quaternized chitosan;

[0007] (2) adding quaternized chitosan to deionized water, adjusting the pH to 3.5-4.5 with acetic acid solution, adding potassium periodate, stirring and reacting at room temperature in the dark for 3-5 hours, adding anhydrous ethanol to stop the reaction, washing, and drying under reduced pressure to obtain quaternized oxidized chitosan;

[0008] (3) adding quaternized oxidized chitosan to a 37 wt % formaldehyde solution, adding deionized water, adjusting the pH to 10.5-11.5 with a sodium hydroxide solution, adding urea, raising the temperature to 75-85° C., stirring and reacting for 50-70 min, and cooling to obtain a prepolymer solution;

[0009] (4) The pH value of the prepolymer solution is adjusted to 8-9 with formic acid solution, and a formaldehyde solution and urea with a concentration of 37 wt% are added, the temperature is raised to 55-65° C., and the mixture is stirred for reaction for 25-35 min. The pH value is then adjusted to 4.8-5.5 with formic acid solution, and quaternized oxidized chitosan and urea are added, the temperature is raised to 75-85° C., and the mixture is stirred for reaction for 50-70 min. The temperature is then lowered to 55-65° C., urea is added, and the mixture is stirred for 20-40 min. The pH value is adjusted to 7.9-8.3 with sodium hydroxide solution, and the mixture is cooled to room temperature to obtain an antibacterial urea resin.

[0010] Preferably, in step (1), the weight ratio of chitosan, sodium iodide and dimethylaminoethyl chloride hydrochloride is 5-15:20-60:2-8.

[0011] Preferably, the amount of N-methyl-2-pyrrolidone solution used in step (1) is 8-12 times the weight of chitosan.

[0012] Preferably, in step (2), the weight ratio of quaternized chitosan to potassium periodate is 5-15:2-5.

[0013] Preferably, in step (2), the amount of deionized water used is 40-60 times the weight of the quaternized chitosan, and the amount of anhydrous ethanol used is 1.5-3 times the weight of the deionized water.

[0014] Preferably, the concentration of the acetic acid solution in step (2) is 5wt%-15wt%.

[0015] Preferably, the concentration of the sodium hydroxide solution in step (3) and step (4) is 25wt%-35wt%.

[0016] Preferably, in step (3), the weight ratio of quaternized oxidized chitosan, formaldehyde solution, deionized water and urea is 1-3:15-25:22-38:12-21.

[0017] Preferably, in step (4), the weight ratio of the prepolymer solution, the formaldehyde solution, the quaternized oxidized chitosan and the urea is 50-90:58-98:6-10:35-55.

[0018] Preferably, the concentration of the formic acid solution in step (4) is 45wt%-55wt%

[0019] Preferably, in step (4), urea is added in a weight ratio of 15-25:15-25:5 in sequence.

[0020] Furthermore, the present invention also provides an antibacterial urea resin obtained by the preparation method of the antibacterial urea resin.

[0021] Beneficial effects of the present invention:

[0022] The present invention significantly improves the comprehensive performance of urea resin by introducing oxidized quaternized chitosan, including higher solid content and viscosity, moderate curing time and excellent antibacterial performance, while greatly reducing the free formaldehyde content. The environmental performance and safety of the resin are significantly improved, meeting more stringent environmental protection requirements. The plywood prepared by using the antibacterial urea resin has a bonding strength of more than 1MPa, meeting the use requirements of national Class II plywood, and the formaldehyde emission is as low as 0.5mg / L, which significantly reduces the harm to human health and indoor air quality, meets green environmental protection standards, and is suitable for fields with high environmental protection requirements such as interior decoration and furniture manufacturing.

[0023] The oxidized quaternized chitosan provided by the present invention forms cross-linking sites through its active aldehyde groups, and is cross-linked in the urea resin network, thereby improving the dispersibility and cohesion of chitosan in the resin, significantly improving the bonding strength of the resin, and reducing the amount of formaldehyde used, reducing the free formaldehyde content and the formaldehyde release. In addition, the batch addition of quaternized oxidized chitosan effectively avoids the excessively rapid reaction of urea and aldehyde groups, prevents chitosan from agglomerating to form insoluble aggregates, thereby further reducing the free formaldehyde content, and at the same time improving the antibacterial property and adhesive property of the resin.

[0024] In summary, the present invention not only significantly improves the basic properties of urea resin by optimizing the formula and process, but also gives it excellent antibacterial properties and environmental protection characteristics. The prepared plywood has the characteristics of high strength and low formaldehyde emission, is suitable for a variety of application scenarios with high environmental protection requirements, and has broad market prospects. DETAILED DESCRIPTION

[0025] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0026] Embodiment 1:

[0027] (1) Add 5 g of chitosan to 40 g of N-methyl-2-pyrrolidone solution containing 0.8 wt% acetic acid, stir for 20 min, then add 20 g of sodium iodide, heat to 55° C., stir for 20 min, then add 2 g of dimethylaminoethyl chloride hydrochloride, continue stirring for 2.5 h, finally wash with anhydrous ethanol 3 times, wash with acetone 3 times, and dry under reduced pressure to obtain quaternized chitosan;

[0028] (2) 5 g of quaternized chitosan was added to 200 g of deionized water, and the pH was adjusted to 4.4 with a 5 wt % acetic acid solution, and then 2 g of potassium periodate was added. The mixture was stirred and reacted for 3 h at room temperature in the dark, and 300 g of anhydrous ethanol was added to stop the reaction. Finally, the mixture was washed with deionized water 3 times, and anhydrous ethanol 3 times, and dried under reduced pressure to obtain quaternized oxidized chitosan;

[0029] (3) adding 1 g of quaternized oxidized chitosan to 15 g of a 37 wt % formaldehyde solution, adding 22 g of deionized water, adjusting the pH to 10.5 with a 25 wt % sodium hydroxide solution, then adding 12 g of urea, heating to 75° C., stirring for 50 min, and cooling to obtain a prepolymer solution;

[0030] (4) The pH value of 50 g of the prepolymer solution was adjusted to 8.1 with a formic acid solution having a concentration of 45 wt%, and 58 g of a formaldehyde solution having a concentration of 37 wt% and 15 g of urea were added. The temperature was raised to 55° C. and stirred for reaction for 20 min. The pH value was then adjusted to 3.5 with a formic acid solution having a concentration of 50 wt%, and 6 g of quaternized oxidized chitosan and 15 g of urea were added. The temperature was raised to 75° C. and stirred for reaction for 50 min. The temperature was then lowered to 55° C., and 5 g of urea was added. The mixture was stirred for 20 min. The pH value was adjusted to 7.9 with a sodium hydroxide solution having a concentration of 20 wt%, and the mixture was cooled to room temperature to obtain an antibacterial urea resin.

[0031] Embodiment 2:

[0032] (1) 10 g of chitosan was added to 100 g of N-methyl-2-pyrrolidone solution containing 1 wt% acetic acid, stirred for 30 min, then 40 g of sodium iodide was added, the temperature was raised to 60° C., stirred for 30 min, then 4.5 g of dimethylaminoethyl chloride hydrochloride was added, and the stirring reaction was continued for 3 h. Finally, the mixture was washed with anhydrous ethanol 3 times, washed with acetone 3 times, and dried under reduced pressure to obtain quaternized chitosan;

[0033] (2) 10 g of quaternized chitosan was added to 500 g of deionized water, and the pH was adjusted to 4.0 with a 10 wt % acetic acid solution, and then 3 g of potassium periodate was added. The mixture was stirred and reacted for 4 h at room temperature in the dark, and 1000 g of anhydrous ethanol was added to stop the reaction. Finally, the mixture was washed with deionized water 3 times, and anhydrous ethanol 3 times, and dried under reduced pressure to obtain quaternized oxidized chitosan;

[0034] (3) adding 2 g of quaternized oxidized chitosan to 20 g of a 37 wt % formaldehyde solution, adding 30 g of deionized water, adjusting the pH to 11 with a 30 wt % sodium hydroxide solution, then adding 15 g of urea, heating to 80° C., stirring for 60 min, and cooling to obtain a prepolymer solution;

[0035] (4) The pH value of 70 g of the prepolymer solution was adjusted to 8.5 with a 50 wt % formic acid solution, 75 g of a 37 wt % formaldehyde solution and 20 g of urea were added, the temperature was raised to 60° C., and the mixture was stirred for reaction for 30 min. The pH value was then adjusted to 5.2 with a 50 wt % formic acid solution, 8 g of quaternized oxidized chitosan and 20 g of urea were added, the temperature was raised to 80° C., and the mixture was stirred for reaction for 60 min. The temperature was then lowered to 60° C., 5 g of urea was added, and the mixture was stirred for 30 min. The pH value was adjusted to 8.1 with a 30 wt % sodium hydroxide solution, and the mixture was cooled to room temperature to obtain an antibacterial urea resin.

[0036] Embodiment 3:

[0037] (1) 15 g of chitosan was added to 180 g of N-methyl-2-pyrrolidone solution containing 1.2 wt% acetic acid, stirred for 40 min, then 60 g of sodium iodide was added, the temperature was raised to 65° C., stirred for 40 min, then 8 g of dimethylaminochloroethane hydrochloride was added, the reaction was continued with stirring for 4 h, and finally the solution was washed with anhydrous ethanol 3 times, washed with acetone 3 times, and dried under reduced pressure to obtain quaternized chitosan;

[0038] (2) 15 g of quaternized chitosan was added to 900 g of deionized water, and the pH was adjusted to 4.5 with a 15 wt % acetic acid solution, and then 5 g of potassium periodate was added. The mixture was stirred and reacted for 5 h at room temperature in the dark, and 2700 g of anhydrous ethanol was added to stop the reaction. Finally, the mixture was washed with deionized water 3 times, and with anhydrous ethanol 3 times, and dried under reduced pressure to obtain quaternized oxidized chitosan;

[0039] (3) adding 3 g of quaternized oxidized chitosan to 25 g of a 37 wt % formaldehyde solution, adding 38 g of deionized water, adjusting the pH to 11.4 with a 35 wt % sodium hydroxide solution, then adding 21 g of urea, heating to 85° C., stirring for 70 min, and cooling to obtain a prepolymer solution;

[0040] (4) The pH value of 90 g of the prepolymer solution was adjusted to 8.5 with a 55 wt % formic acid solution, 98 g of a 37 wt % formaldehyde solution and 25 g of urea were added, the temperature was raised to 65° C., and the mixture was stirred for reaction for 40 min. The pH value was then adjusted to 5.5 with a 50 wt % formic acid solution, 10 g of quaternized oxidized chitosan and 25 g of urea were added, the temperature was raised to 85° C., and the mixture was stirred for reaction for 70 min. The temperature was then lowered to 65° C., 5 g of urea was added, and the mixture was stirred for 40 min. The pH value was adjusted to 8.3 with a 35 wt % sodium hydroxide solution, and the mixture was cooled to room temperature to obtain an antibacterial urea resin.

[0041] Comparative Example 1:

[0042] The difference between Comparative Example 1 and Example 2 is that the quaternized oxidized chitosan in step (3) and step (4) is replaced by quaternized chitosan;

[0043] The specific steps are as follows:

[0044] (1) 10 g of chitosan was added to 100 g of N-methyl-2-pyrrolidone solution containing 1 wt% acetic acid, stirred for 30 min, then 40 g of sodium iodide was added, the temperature was raised to 60° C., stirred for 30 min, then 4.5 g of dimethylaminoethyl chloride hydrochloride was added, and the stirring reaction was continued for 3 h. Finally, the mixture was washed with anhydrous ethanol 3 times, washed with acetone 3 times, and dried under reduced pressure to obtain quaternized chitosan;

[0045] (2) adding 2 g of quaternized chitosan to 20 g of a 37 wt % formaldehyde solution, adding 30 g of deionized water, adjusting the pH to 11 with a 30 wt % sodium hydroxide solution, then adding 15 g of urea, heating to 80° C., stirring for 60 min, and cooling to obtain a prepolymer solution;

[0046] (3) The pH value of 70 g of the prepolymer solution was adjusted to 8.5 with a 50 wt % formic acid solution, 75 g of a 37 wt % formaldehyde solution and 20 g of urea were added, the temperature was raised to 60° C., and the mixture was stirred for reaction for 30 min. The pH value was then adjusted to 5.2 with a 50 wt % formic acid solution, 8 g of quaternized chitosan and 20 g of urea were added, the temperature was raised to 80° C., the mixture was stirred for reaction for 60 min, the temperature was lowered to 60° C., 5 g of urea was added, the mixture was stirred for 30 min, the pH value was adjusted to 8.1 with a 30 wt % sodium hydroxide solution, and the mixture was cooled to room temperature to obtain a urea resin.

[0047] Comparative Example 2:

[0048] The difference between Comparative Example 2 and Example 2 is that: the amount of quaternized oxidized chitosan used in step (3) is 10 g, and quaternized oxidized chitosan is not added in step (4);

[0049] The specific steps are as follows:

[0050] (1) 10 g of chitosan was added to 100 g of N-methyl-2-pyrrolidone solution containing 1 wt% acetic acid, stirred for 30 min, then 40 g of sodium iodide was added, the temperature was raised to 60° C., stirred for 30 min, then 4.5 g of dimethylaminoethyl chloride hydrochloride was added, and the stirring reaction was continued for 3 h. Finally, the mixture was washed with anhydrous ethanol 3 times, washed with acetone 3 times, and dried under reduced pressure to obtain quaternized chitosan;

[0051] (2) 10 g of quaternized chitosan was added to 500 g of deionized water, and the pH was adjusted to 4.0 with a 10 wt % acetic acid solution, and then 3 g of potassium periodate was added. The mixture was stirred and reacted for 4 h at room temperature in the dark, and 1000 g of anhydrous ethanol was added to stop the reaction. Finally, the mixture was washed with deionized water 3 times, and anhydrous ethanol 3 times, and dried under reduced pressure to obtain quaternized oxidized chitosan;

[0052] (3) adding 10 g of quaternized oxidized chitosan to 20 g of a 37 wt % formaldehyde solution, adding 30 g of deionized water, adjusting the pH to 11 with a 30 wt % sodium hydroxide solution, then adding 15 g of urea, heating to 80° C., stirring for 60 min, and cooling to obtain a prepolymer solution;

[0053] (4) The pH value of 70 g of the prepolymer solution was adjusted to 8.5 with a 50 wt % formic acid solution, 75 g of a 37 wt % formaldehyde solution and 20 g of urea were added, the temperature was raised to 60° C., and the mixture was stirred for reaction for 30 min. The pH value was then adjusted to 5.2 with a 50 wt % formic acid solution, 20 g of urea was added, the temperature was raised to 80° C., and the mixture was stirred for reaction for 60 min. The temperature was then lowered to 60° C., 5 g of urea was added, and the mixture was stirred for 30 min. The pH value was adjusted to 8.1 with a 30 wt % sodium hydroxide solution, and the mixture was cooled to room temperature to obtain a urea resin.

[0054] Comparative Example 3:

[0055] The difference between Comparative Example 3 and Example 2 is that: the amount of quaternized oxidized chitosan used in step (4) is 10 g, and quaternized oxidized chitosan is not added in step (3);

[0056] The specific steps are as follows:

[0057] (1) 10 g of chitosan was added to 100 g of N-methyl-2-pyrrolidone solution containing 1 wt% acetic acid, stirred for 30 min, then 40 g of sodium iodide was added, the temperature was raised to 60° C., stirred for 30 min, then 4.5 g of dimethylaminoethyl chloride hydrochloride was added, and the stirring reaction was continued for 3 h. Finally, the mixture was washed with anhydrous ethanol 3 times, washed with acetone 3 times, and dried under reduced pressure to obtain quaternized chitosan;

[0058] (2) 10 g of quaternized chitosan was added to 500 g of deionized water, and the pH was adjusted to 4.0 with a 10 wt % acetic acid solution, and then 3 g of potassium periodate was added. The mixture was stirred and reacted for 4 h at room temperature in the dark, and 1000 g of anhydrous ethanol was added to stop the reaction. Finally, the mixture was washed with deionized water 3 times, and anhydrous ethanol 3 times, and dried under reduced pressure to obtain quaternized oxidized chitosan;

[0059] (3) 20 g of a 37 wt % formaldehyde solution and 30 g of deionized water were mixed, the pH was adjusted to 11 with a 30 wt % sodium hydroxide solution, and then 15 g of urea was added. The mixture was heated to 80° C., stirred for reaction for 60 min, and cooled to obtain a prepolymer solution.

[0060] (4) The pH value of 70 g of the prepolymer solution was adjusted to 8.5 with a 50 wt % formic acid solution, 75 g of a 37 wt % formaldehyde solution and 20 g of urea were added, the temperature was raised to 60° C., and the mixture was stirred for reaction for 30 min. The pH value was then adjusted to 5.2 with a 50 wt % formic acid solution, 10 g of quaternized oxidized chitosan and 20 g of urea were added, the temperature was raised to 80° C., the mixture was stirred for reaction for 60 min, the temperature was then lowered to 60° C., 5 g of urea was added, the mixture was stirred for 30 min, the pH value was adjusted to 8.1 with a 30 wt % sodium hydroxide solution, and the mixture was cooled to room temperature to obtain a urea resin.

[0061] Comparative Example 4:

[0062] The difference between Comparative Example 4 and Example 2 is that: quaternized oxidized chitosan is not added in step (3) and step (4);

[0063] The specific steps are as follows:

[0064] (1) 10 g of chitosan was added to 100 g of N-methyl-2-pyrrolidone solution containing 1 wt% acetic acid, stirred for 30 min, then 40 g of sodium iodide was added, the temperature was raised to 60° C., stirred for 30 min, then 4.5 g of dimethylaminoethyl chloride hydrochloride was added, and the stirring reaction was continued for 3 h. Finally, the mixture was washed with anhydrous ethanol 3 times, washed with acetone 3 times, and dried under reduced pressure to obtain quaternized chitosan;

[0065] (2) 10 g of quaternized chitosan was added to 500 g of deionized water, and the pH was adjusted to 4.0 with a 10 wt % acetic acid solution, and then 3 g of potassium periodate was added. The mixture was stirred and reacted for 4 h at room temperature in the dark, and 1000 g of anhydrous ethanol was added to stop the reaction. Finally, the mixture was washed with deionized water 3 times, and anhydrous ethanol 3 times, and dried under reduced pressure to obtain quaternized oxidized chitosan;

[0066] (3) 20 g of a 37 wt % formaldehyde solution and 30 g of deionized water were mixed, the pH was adjusted to 11 with a 30 wt % sodium hydroxide solution, and then 15 g of urea was added. The mixture was heated to 80° C., stirred for reaction for 60 min, and cooled to obtain a prepolymer solution.

[0067] (4) The pH value of 70 g of the prepolymer solution was adjusted to 8.5 with a 50 wt % formic acid solution, 75 g of a 37 wt % formaldehyde solution and 20 g of urea were added, the temperature was raised to 60° C., and the mixture was stirred for reaction for 30 min. The pH value was then adjusted to 5.2 with a 50 wt % formic acid solution, 20 g of urea was added, the temperature was raised to 80° C., and the mixture was stirred for reaction for 60 min. The temperature was then lowered to 60° C., 5 g of urea was added, and the mixture was stirred for 30 min. The pH value was adjusted to 8.1 with a 30 wt % sodium hydroxide solution, and the mixture was cooled to room temperature to obtain a urea resin.

[0068] Performance Test:

[0069] Basic performance testing: solid content, viscosity, curing time, free formaldehyde content were tested according to GB / T14074-2006 standard. The results are shown in Table 1.

[0070] Preparation of plywood: The urea resin prepared in the examples and comparative examples was used as the main adhesive, 1% of the resin mass of ammonium chloride was added as a curing agent, and 20% of flour was used as a filler to prepare the adhesive. Manual coating was used, and the core board was glued on both sides, with a glue amount of 300g / m 2 After gluing, aging and assembly, the veneer was hot pressed at a temperature of 120°C. The prepared plywood was placed in a constant temperature and humidity environment at a temperature of 20±2°C and a humidity of 65±2% for one week before the plywood performance was measured.

[0071] The bonding strength and formaldehyde emission test of plywood is carried out according to GB / T17657-2013 standard, and the bonding strength is tested according to the standard method for Class II plywood.

[0072] Antibacterial performance test: Separate the plywood layers and drip 8×10 5 4 ml of Escherichia coli solution with a concentration of cfu / mL was used as a control, and a blank control sample was used as a control. The culture time was transferred to a constant temperature and humidity chamber for 24 hours. The temperature was controlled at 38°C and the relative humidity was 95%. The antibacterial rate was calculated by the plate count method. The results are shown in Table 1.

[0073] Table 1 Performance test results

[0074]

[0075] Data Analysis:

[0076] From the data of Examples 1-3 in Table 1, it can be seen that the antibacterial urea resin prepared by the present invention has a high solid content and viscosity, a moderate curing time and excellent antibacterial properties, and most importantly, has an extremely low free formaldehyde content, which helps to reduce environmental pollution, improve the environmental performance of the product, enhance the safety of use, and meet more stringent environmental protection requirements. The plywood prepared using the antibacterial urea resin has a bonding strength of more than 1MPa, which can meet the use requirements of Class II plywood in the national standard, and the formaldehyde emission is as low as 0.5mg / L. The extremely low formaldehyde emission can significantly reduce the harm to human health and indoor air quality, meet the green environmental protection standards, and is suitable for scenes with high environmental protection requirements, such as interior decoration and furniture manufacturing.

[0077] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that the oxidized quaternized chitosan helps to increase the solid content and viscosity of the antibacterial urea resin, and can further improve the antibacterial performance. This is mainly because the oxidized quaternized chitosan has active aldehyde groups, which can form cross-linking sites and cross-link in the urea resin network, thereby effectively improving the dispersion of the quaternized chitosan in the urea resin, thereby improving the comprehensive performance of the urea resin, and the cross-linked quaternized chitosan can provide higher cohesion, so that the plywood prepared therefrom has higher bonding strength. Furthermore, the active aldehyde groups of the oxidized quaternized chitosan can effectively reduce the amount of formaldehyde used, thereby reducing the free formaldehyde content and reducing the formaldehyde release of the plywood.

[0078] It can be seen from the data of Example 2 and Comparative Examples 2-3 in Table 1 that the batch addition of quaternized oxidized chitosan can effectively improve the comprehensive properties of the antibacterial urea resin, especially the antibacterial property and the free formaldehyde content. This is mainly because the batch addition of quaternized oxidized chitosan helps to avoid too rapid reaction between urea and aldehyde groups, resulting in agglomeration of the quaternized oxidized chitosan, thereby forming insoluble agglomerates, resulting in a large amount of free formaldehyde in the agglomerates, which are difficult to react with urea, thereby resulting in an increase in the free formaldehyde content. In addition, after being prepared into plywood, the adhesive properties decrease and the formaldehyde release increases.

[0079] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that quaternized oxidized chitosan can effectively optimize the basic properties of urea resin and impart it with strong antibacterial properties, and reduce formaldehyde emission while improving bonding strength.

[0080] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing an antibacterial urea resin, characterized in that: The following steps are involved: (1) adding chitosan to an N-methyl-2-pyrrolidone solution containing 0.8 wt%-1.2 wt% acetic acid, stirring for 20-40 min, then adding sodium iodide, heating to 55-65° C., stirring for 20-40 min, then adding dimethylaminoethyl chloride hydrochloride, continuing to stir for 2.5-3.5 h, finally washing, and drying under reduced pressure to obtain quaternized chitosan; (2) adding quaternized chitosan to deionized water, adjusting the pH to 3.5-4.5 with acetic acid solution, adding potassium periodate, stirring and reacting at room temperature in the dark for 3-5 hours, adding anhydrous ethanol to stop the reaction, washing, and drying under reduced pressure to obtain quaternized oxidized chitosan; (3) adding quaternized oxidized chitosan to a 37 wt % formaldehyde solution, adding deionized water, adjusting the pH to 10.5-11.5 with a sodium hydroxide solution, adding urea, raising the temperature to 75-85° C., stirring and reacting for 50-70 min, and cooling to obtain a prepolymer solution; (4) adjusting the pH value of the prepolymer solution to 8-9 with formic acid solution, adding formaldehyde solution and urea with a concentration of 37 wt%, heating to 55-65° C., stirring and reacting for 25-35 min, then adjusting the pH value to 4.8-5.5 with formic acid solution, adding quaternized oxidized chitosan and urea, heating to 75-85° C., stirring and reacting for 50-70 min, then cooling to 55-65° C., adding urea, stirring for 20-40 min, adjusting the pH value to 7.9-8.3 with sodium hydroxide solution, cooling to room temperature, and obtaining an antibacterial urea resin; In the step (1), the weight ratio of chitosan, sodium iodide and dimethylaminoethyl chloride hydrochloride is 5-15:20-60:2-8; In the step (3), the weight ratio of quaternized oxidized chitosan, formaldehyde solution, deionized water and urea is 1-3:15-25:22-38:12-21; In the step (4), the weight ratio of the prepolymer solution, the formaldehyde solution, the quaternized oxidized chitosan and the urea is 50-90:58-98:6-10:35-55.

2. The method for preparing the antibacterial urea resin according to claim 1, characterized in that: The amount of N-methyl-2-pyrrolidone solution used in step (1) is 8-12 times the weight of chitosan.

3. The method for preparing the antibacterial urea resin according to claim 1, characterized in that: In the step (2), the weight ratio of quaternized chitosan to potassium periodate is 5-15:2-5.

4. The method for preparing the antibacterial urea resin according to claim 1, characterized in that: In the step (2), the amount of deionized water used is 40-60 times the weight of the quaternized chitosan, and the amount of anhydrous ethanol used is 1.5-3 times the weight of the deionized water.

5. The method for preparing the antibacterial urea resin according to claim 1, characterized in that: The concentration of the acetic acid solution in step (2) is 5wt%-15wt%.

6. The method for preparing the antibacterial urea resin according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (3) and step (4) is 25wt%-35wt%.

7. The method for preparing the antibacterial urea resin according to claim 1, characterized in that: The concentration of the formic acid solution in step (4) is 45wt%-55wt%.

8. The method for preparing the antibacterial urea resin according to claim 1, characterized in that: In the step (4), the urea is added in the order of weight ratio of 15-25:15-25:

5.

9. An antibacterial urea resin, characterized in that: The antibacterial urea resin is obtained by the preparation method of any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for preparing post-crosslinking modified urea-formaldehyde resin adhesive

    CN101311200A

  • Preparation method of low crystalline, mildew-proof and water-resistant urea resin

    CN107325242A

  • Novel mildewproof resin bonding agent and preparation method thereof

    CN107936889A

  • Chitosan modified melamine resin adhesive and preparation method thereof

    CN114058303A

  • VN25457A